(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
The present study aims to assess the impact of the green campus score indicator on the development of sports infrastructure at Universitas Papua, Manokwari. The assessment method for implementing a green campus using UI GreenMetric as the criteria met the specified score standard. The analysis findings indicated that the implementation is adequate, following the green campus indicator analysis on the UNIPA Campus’s sports center infrastructure. There are only a few indicators that need to be improved in constructing a sports center, such as managing and monitoring development implementation, the use of environmentally friendly tools, managing and monitoring the impacts caused by development activities, and the campus providing regular budgets. In addition, other indicators are thought to have been well field implemented. Based on these findings, a strategy for environmental structuring and green campus infrastructure is required for the UNIPA campus sports center infrastructure. The strategy emphasizes the importance of paying attention to potential threats that may arise as a result of construction, such as environmental damage, the emergence of new residential clusters that do not follow the UNIPA campus, and the emergence of new residential clusters that do not follow the UNIPA campus.